Air temperature and precipitation evolution in the area of Keszthely - Németh-Koczó, Johanna; Anda, Angéla (GEORGIKON FOR AGRICULTURE, 2019)
In this brief study some local signs of global climate modification are presented based on the statistical analysis of long-term air temperature and precipitation data for Keszthely (Hungary). In the Agrometeorological Research Station in Keszthely continuous meteorological measurements have been recorded since 1871, therefore an adequate length of data is available for analysis. Based on our results, a significant warming tendency is dominant, an increasing trend in air temperature can be established especially from the 1980s. Over the 116-year study period, statistically significant increase of 0.1°C per decade was found with 9.94±0.77°C annual average. Regarding to rainfall a downward trend of 47 mm per 100 years was observed. Keywords: air temperature, rainfall, climate change, time-series analysis, Keszthely (Hungary)
Keywords: air temperature; climate change; time-series analysis; Keszthely (Hungary)